Treatment of convulsive status epilepticus in Brazil: a review - Luis Otavio Caboclo (Arquivos de Neuro-Psiquiatria)
Status epilepticus (SE) is the most severe presentation of epilepsy. Currently, SE is defined according to 2 sequential time frames: time 1, after which it is unlikely that the seizure will resolve spontaneously, therefore requiring the initiation of therapy; and time 2, when long-term consequences become more likely. For convulsive SE, these time frames are well defined: 5 minutes for time 1 and 30 minutes for time 2. “Time is brain” in the treatment of SE, as delays in diagnosis and treatment are associated with worse outcomes. After clinical stabilization, the first step is the administration of intravenous (IV) benzodiazepines. Rapid initiation of treatment and use of appropriate dosing are more important than the selection of a specific benzodiazepine. Following this, treatment continues with the use of an IV antiseizure medication (ASM). In Brazil, the recommended options available are phenytoin and levetiracetam. Status epilepticus is considered refractory to treatment if seizures persist after the administration of benzodiazepines and IV ASM. The cornerstone of this stage is the induction of therapeutic coma using IV anesthetic drugs (IVADs), although evidence is limited regarding the choice among midazolam, propofol, or barbiturates. Super-refractory SE is defined when seizures persist despite continuous infusion of IVADs or recur after these drugs are tapered. There is very limited data regarding the treatment of super-refractory SE. In the absence of randomized controlled trials, treatment should be guided by the physician's experience, clinical judgment, and established therapeutic options from previous reports.